Oracle GoldenGate 11g handbook - Freeman, Robert G. 1965- (McGraw Hill Education ;, 2013)
Showing you how to use Oracle GoldenGate step-by-step; this authoritative book features hands-on workshops that will explain how to install; configure; and implement this high-performance application. --
Includes index. - Online resource; title from title page (Safari, viewed Sept. 04, 2013)
Keywords: Oracle; Database management; Data transmission systems; Electronic data processing; Database design; Bases de données; Gestion; Bases de données; Conception